Insights on Investment Psychology of Individual Investors at Dhaka Stock Exchange (DSE) During The Covid-19 Pandemic - Muzareba AM; Hossain T; Nesa Z (Universitas Djuanda, 2023)
Almost all calamities make a footmark on the financial sector, and COVID-19 is no different. On this ground, stock market investors' attitudes, thinking, and everything receives severe attention as investors' psychology is a common determinant of the trading activity and investment decisions which ultimately drive the market. Investors in developing countries like Bangladesh need a more rigorous analysis of their behavior as they are now more concerned and worried about their investments than before. They must be more vigilant in terms of preparation to eliminate the impacts of COVID-19. This paper aims at focusing on understanding how the spread of the pandemic is reshaping the psychological aspect of investors with a focus on four selected factors, risk perception, market psychology, media effect, and loss aversion. Three hundred eighty-five responses were collected through a questionnaire during the COVID-19 pandemic, where data was tested using Smart PLS 3.0 in conjunction with IBM SPSS 25. With the help of the measurement model and structural model of partial least square, the suggested framework in this paper has been studied to identify some aspects of investors' psychology that could potentially have insights and information on how countries should place themselves to respond to future epidemics. The effect size and individual t-test of the factors explain the affected state of thinking of retail investors, where loss aversion and risk perception affect investors the most. In contrast, media effects have a moderate influence, and market psychology has the least. The findings are expected to help investors and policymakers understand the behavior of the market and prepare accordingly for challenging the upcoming economic crisis in the corona war.